Law Enforcement Against the Crime of Murder Motivated by Infidelity - Reston N.A Laia, Yohanes; Rahman Maulana Siregar, Abdul; Sumarno (International Conference Epicentrum of Economic Global Framework, 2026)
Premeditated murder is a grave offense under criminal law, as it fundamentally deprives an individual of their right to life. Infidelity is a frequent underlying motive for this crime, often triggered by emotional factors such as jealousy, interpersonal conflict, and feelings of hurt. Consequently, this study aims to analyze law enforcement regarding premeditated murder motivated by infidelity and to examine the criminal liability of the perpetrators, supported by case studies. The research employs a normative-juridical method, utilizing both statutory and case-based approaches. The findings confirm that premeditated murder is explicitly regulated under Article 459 of Law Number 1 of 2023 concerning the Criminal Code; this article stipulates that anyone who intentionally takes another person's life with premeditation is subject to the death penalty, life imprisonment, or a fixed-term prison sentence. This provision indicates that the element of premeditation is a primary indicator of the high degree of the perpetrator's culpability. However, in practice, judges consider various aspects such as the motive, the perpetrator's psychological state, mitigating and aggravating circumstances, and the social impact of the act. Thus, consistency in the application of the law is essential to achieve justice, legal certainty, and legal utility.